ACUTE UPPER GASTROINTESTINAL BLEEDING IN PATIENTS WITH CIRRHOSIS: ENDOSCOPIC FINDINGS - Muhammad Abdur Rahman Afridi,; Umme Salma Rashid,; Hassan, Muhammad Kamran; Muhammad Fahim Afridi, (Journal of Postgraduate Medical Institute, 2023)
Objective: To determine the endoscopic findings in liver cirrhosis patients presenting with upper gastrointestinal bleeding. Methodology: A descriptive observational study of 152 patients, of either gender, having liver cirrhosis presenting with acute upper gastrointestinal bleeding was conducted in the Department of Medicine, Lady Reading Hospital Peshawar, from July 2020 to December 2020. Demographic details were noted and relevant investigations were carried out. After resuscitation and stabilization, all patients were subjected to upper gastrointestinal endoscopy by a consultant gastroenterologist to detect endoscopic lesions causing upper gastrointestinal bleeding (UGIB). SPSS version 21 was used for data entry and analysis; post-stratification chi-square (x2) with p<0.05 was considered statistically significant. Results: The mean age of 152 patients was 50.95±16.44 years, including 96 (63.2%) males and 56 (36.8%) females. Oesophageal varices were found in 133 (87.5%) patients, gastric varices in 41 (27%) and portal gastropathy in 57 (37.5%) patients. Non-variceal lesions included peptic ulcer disease in 21 (13.8%) patients and gastritis in 19 (12.5%) patients. Only 5 (3.3%) patients had normal endoscopic study. Oesophageal varices were more common in males (72% versus 28%; p=0.001) whereas, gastric varices were more common in female patients (56% versus 44%), which was statistically significant (p=0.003). Conclusion: Portal hypertension related lesions were the most common underlying etiology in the study patients of liver cirrhosis, presenting with UGIB. The findings on endoscopy included oesophageal varices (87.5%), portal gastropathy (37.5%) and gastric varices (27%). Non-variceal lesions were peptic ulcer disease (13.8%) and gastritis (12.5%). Male gender had significant association with esophageal varices and female gender with gastric varices.